2022
DOI: 10.13057/biodiv/d230945
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecology of Pteridophytes in Cendil heath forest and Gurok Beraye tropical rainforest, Belitung Island, Indonesia

Abstract: Abstract. Priambudi AS, Chikmawati T, Sulistijorini, Fakhrurrozi Y. 2022. Diversity and ecology of Pteridophytes in Cendil heath forest and Gurok Beraye tropical rainforest, Belitung, Indonesia. Biodiversitas 23: 4775-4782. The tropical heath forest is a unique ecosystem type characterized by sandy and acidic soils with poor nutrients and water availability, making this ecosystem very vulnerable to disturbances. Yet, knowledge regarding the diversity and ecology of the biological elements of heath forests is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…That is why Pteridophyta has a role as environmental bioindicators. This result has a higher Margalef Species Richness Index than Priambudi et al (2022) in Belitung Island, which showed the Margalef Species Richness Index value of Pteridophytes in the heath forest (low category 1.29) and tropical rain forest (moderate category 3.36) was below the species richness in karst ecosystems. According to (Ansari et al 2017), several plants from different divisions of the plant kingdom, such as chlorophyta, Bryophyta, and Pteridophyta, can be used to monitor and assess water quality in freshwater or marine, lentic or lotic, wetlands and coastal aquatic ecosystems.…”
Section: Diversitymentioning
confidence: 79%
See 3 more Smart Citations
“…That is why Pteridophyta has a role as environmental bioindicators. This result has a higher Margalef Species Richness Index than Priambudi et al (2022) in Belitung Island, which showed the Margalef Species Richness Index value of Pteridophytes in the heath forest (low category 1.29) and tropical rain forest (moderate category 3.36) was below the species richness in karst ecosystems. According to (Ansari et al 2017), several plants from different divisions of the plant kingdom, such as chlorophyta, Bryophyta, and Pteridophyta, can be used to monitor and assess water quality in freshwater or marine, lentic or lotic, wetlands and coastal aquatic ecosystems.…”
Section: Diversitymentioning
confidence: 79%
“…For unknown Pteridophyta species, the names will be identified using Hoshizaki and Moran (2001), Mehltreter et al (2010), andCallado et al (2016). The detailed morphological generative (spore) and vegetative (leaf, stem, rhizome, hair/scale) organs were documented for each species found (Priambudi et al 2022). Name validation is carried out by checking the scientific name on the website of the Global Biodiversity Information Facility (GBIF) (https://www.gbif.org/).…”
Section: Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Belitung Islands lie between Sumatra and Borneo in Indonesia and are part of the savanna corridor in Sundaland [10]. The ecosystem in Belitung Islands comprises mainly the heath forest, which stands almost entirely on Belitung Island [11] with small areas of lowland rainforests [12]. As an archipelago, the Belitung Islands also have an extensive mangrove forest ecosystem, which is a species-rich community [13].…”
Section: Introductionmentioning
confidence: 99%